2014
DOI: 10.1111/aji.12226
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Understanding Endometrial Receptivity: Molecular Basis and Clinical Applications

Abstract: Advancement in the field of ART has lead to the possibility of achieving good quality embryos. However, the success rate in ART needs further improvement. This is largely dependent on identifying the receptive endometrium for the successful implantation of embryos as well as modulating the endometrium to the receptive stage. In the last half-a-decade, focus has been shifting toward identifying the receptive endometrium. Here, we summarize different tools explored to identify receptive endometrium from the lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 92 publications
1
44
0
1
Order By: Relevance
“…[5,6] and consequently lower pregnancy rates. It is theorized that possible mechanisms that may alter embryo-endometrium synchrony may include a premature elevation of progesterone that could alter the normal endometrial window of implantation [3,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6] and consequently lower pregnancy rates. It is theorized that possible mechanisms that may alter embryo-endometrium synchrony may include a premature elevation of progesterone that could alter the normal endometrial window of implantation [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, previous studies comparing fresh embryo transfer (ET) with FET are limited due to the morphological differences in their study cohorts. Despite this fact, some studies have reported even higher pregnancy rates following a FET compared to fresh transfers [3,6,7]. In addition, with the advances and optimization made in cryopreservation methods [8], the quality of the frozen embryos and their reproductive potential are at least similar to those observed with fresh embryos [9].…”
Section: Introductionmentioning
confidence: 99%
“…Improved endometrial receptivity is responsible for increased pregnancy rates and reduced early pregnancy failure (30,31). Cytokines and growth factors are associated with endometrial receptivity and implantation (32,33). Thus, the present study measured the levels of GDF-9, integrin αVβ3, TGF-β1, LIF, G-CSF and VEGF in the follicular fluid and endometria of patients with POR.…”
Section: Discussionmentioning
confidence: 93%
“…Część z nich, po zapłodnieniu, zostaje wprowadzonych do jamy macicy celem ich implantacji. Ta hiperstymulacja hormonalna jajników może jednak doprowadzić do zaburzeń w prawidłowym wykształceniu właściwości receptywnych doczesnej, co stanowi obecnie duży problem kliniczny [20][21][22][23].…”
Section: Opis Stanu Wiedzyunclassified